Genomic profiling of a collection of patient-derived xenografts and cell lines identified ixabepilone as an active drug against chemo-resistant osteosarcoma - Maria Cristina Manara; Francesca Bruzzese; Laura Formentini; Lorena Landuzzi; Laura Pazzaglia; Maria Antonella Laginestra; Marianna Carrabotta; Maria Serena Roca; Federica Iannelli; Laura Grumetti; Laura Addi; Alessandro Parra; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Osteosarcoma (OS) shows a multitude of genetic and chromosomal abnormalities together with large biological heterogeneity. These features limited the identification of novel drugs to treat patients with metastases and/or chemo-resistant tumors. The purpose of this study was to create additional resources for drug screening by generating patient-derived xenograft (PDXs) and PDX-derived cell lines that reflect the spectrum of OS heterogeneity. Methods PDXs were derived from OS collected at diagnosis, surgical resections, or metastases. PDX-derived cell lines were also established. Targeted DNA sequencing and digital PCR were applied to identify major genetic alterations. High-throughput drug screening by using a library of 2880-FDA approved compounds and conventional MTT assays were performed to identify the most effective drugs against in vitro and in vivo growth of chemo-resistant OS. Results Targeted DNA sequencing demonstrated alterations in the most commonly amplified oncogenes, such as MYC, CCNE1, DDR2, CDK4, MDM2, and AURKA. Recurrent deletions and SNVs were found in TP53, CDKN2A, RB1, PTEN, and VHL. Copy number variant (CNV) alterations in PDXs, PDX-derived cell lines and xenografts developed from cell lines (CDX) correlated very well with those observed in the matched original human tumors. Drug screenings identified and repurposed five compounds with efficacy against chemoresistant OS. In this context, we prioritized ixabepilone as a drug capable of inducing tumor regression in mice. Conclusions We enriched the scientific community with additional, molecularly characterized OS models to be used for testing novel therapies and supported the inclusion of ixabepilone into treatment plans for chemoresistant OS.